criticism and rhetoric Term in the book of the Norin of the al housri al Kairouani (مجلة إحالات, 2026)
This article deals with the nature of the termsfound in the book of the Norin of the al housri al Kairouani, And tried to stand on the phenomenon of mixingrhetoric and criticism,Because thecriticalter misdefined by the cultural environment on the one hand and by the scientific composition of the critics on the other.